FRI0631 Predictive value of power doppler ultrasonography (PDUS) in the diagnosis of early rheumatoid arthritis. (15th June 2017) - Mayordomo, L; Jurado, C; Velloso, ML; Gutierrez-Leonard, A; González-Moreno, P; Marenco, JL; Almeida, C
Abstract : Background: There is a short window of opportunity for early diagnosis and treatment of rheumatoid arthritis, that may be crucial for reaching remission and a low rate of radiographic progression. High resolution power doppler ultrasonography (PDUS) is helpful in early detection of synovitis and allows an accurate classification of patients with joint inflammation. Objectives: To establish wether the presence of basal power doppler signal in patients with very early arthritis may be helpful in order to establish the risk of final diagnosis of rheumatoid arthritis according ACR criteria 1987 at a year of follow up. Methods: We studied the presence of ultrasonographic Power Doppler (PD) signal on 28 joints (shoulders, elbows, wrists, MCPs, PIPs, knees) and 44 joints (28 joints and in addition hips, ankles, tarsus, and MTPs), with a mid-range equipment GE L5, in 70 patients with suspected early arthritis The patients were included with at least one of the following inclusion criteria: a) Swelling in 2 or more joints b) pain in MCPs, MTPs and/or the wrists c) morning stiffness of more than 30 minutes with <12 months of duration of the symptoms. Presence or not basal erosions (score ≥2 in at least one joint by modified Sharp method) for each patient were registered (65 patients with basal hands and feet radiology available). Presence of RF and ACPA positive were recorded as well. At one year follow-up was established whether patients met criteria for RA according1987 ACR or not. Statistical study: Chi-square, Fisher exact test, p univariant and Odds Ratio calculation. Results: The presence of basal power doppler signal in ≥1 joints of 44 (PD44) in baseline visit shows statistically significant association to RA diagnosis at 12 months by ACR 1987 classification criteria, p=0.003, OR=5, 43 (1, 71–17, 24) but the presence of at least one joint with power doppler signal of 28 joints (PD28) did not (p=0.051). Presence hypertrophic synovium with PD44 or not, in at least one joint (HSORPD44) was associated to RA diagnosis as well p=0.024; OR 10, 24 (1, 12–93, 28). RF was positive in 18/70 (25, 71%) and was associated to RA diagnosis (p 0.003, OR 8, 31 (1, 74–39, 64), as well as FR/ACPA, positive in 20/70 (28, 57%), p=0.001 OR 10 (2, 10–47, 58). PD44 in addition to positive RF was associated to RA p=0.003, OR 12, 93 (1, 59–104, 94). Presence of basal radiographic erosions (BRE) was associated to RA, p=0.001 OR 7, 72 (2, 2–26, 8). PD44 in addition to BRE was significantly associated to RA p=0.0005, OR 29, 33 (3, 61–238, 37). PD28 in addition to RF or BRE was significantly associated to RA respectively p 0.0005 OR 24, 20 (2, 98–196.34) and p=0.003 OR 12, 93 (1, 59–104, 94). Conclusions: The presence of at least one joint with power doppler signal of 44 joints (PD44) on baseline visit may help to predict the RA diagnosis at 12 months of follow up according to criteria ACR 1987, in patients with early RA. PD 44 in addition to classic RA factors (RF and basal radiographic erosions) increased the risk final of RA, till more than three times in case of concomitant basal PD44 and radiographic erosions. Disclosure of Interest: None declared